DISKURSUS “ILLEGITIMATE SEXUAL ACTIVITY” ANAK BANGSA DALAM PERSPEKTIF TABLOID INDONESIA - Nisa Kurnia I (Jurnal Kawistara, 2011)
y “masculine-heterosexual”language, which in this context language is defined absolutely by the state. This paper is intended to dismantle the usage of "masculine-heterosexual" language by the Indonesian mass media when defining and putting illegitimate sexual activity in the landscape of the nation's discourse regarding sexuality. Using critical multiculturalism framework, identity theory and constructivist paradigm, this paper will explore discourse articulated by mass media in articles regarding those matters. Using discourse analysis as the method, a corpus of four tabloids (Tabloid Nova No. 1165/XXIII 21-27 Juni 2010, Tabloid Bintang Edisi 997 Tahun XX Minggu Ketiga Juni 2010, Tabloid Wanita Indonesia No. 1069 21-27 Juni 2010, and Tabloid Genie Edisi 50 Tahun VI, 21-27 Juni 2010) are discussed..